UPAYA GURU DALAM MENANAMKAN KEMANDIRIAN PADA ANAK KELOMPOK BERMAIN ISLAM TERPADU AL USWAH TUBAN - Luluk Munawaroh; An An Andari; Al Fahmi Aji Saputra (UNISAN JURNAL, 2026)
This study aims to describe the efforts of teachers in fostering independence in children at the Integrated Islamic Playgroup Al Uswah Tuban. The study is motivated by the importance of independence as a fundamental aspect of early childhood character development, enabling children to perform daily activities responsibly. This research employs a qualitative descriptive approach, collecting data through observation, interviews, and documentation of teachers, children, and supporting learning materials. The findings indicate that teachers foster independence through habituation, assigning simple responsibilities, applying activity-based learning models, and providing positive reinforcement. These efforts successfully develop children’s independent behaviors, evident in their ability to tidy play equipment, dress themselves, follow daily routines, and make simple decisions independently. The study concludes that teachers play a strategic role in developing children’s independence through consistent, patient, and creative approaches.